PENGARUH PENGGUNAAN PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) PADA PERENDAMAN BENIH TERHADAP PRODUKTIVITAS TANAMAN KEDELAI (Glycine Max L. Merril) - I Gede Rian Pramarta; Ngakan Made Adi Wedagama; Mutia Rahmah; Daniar Nastiti Ayunani (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
Soybean needs continue to increase every year, while soybean productivity cannot meet it, causing the need for efforts so that the growth and yield of soybean plants can be increased. Continuous use of chemical fertilizers can reduce soil quality therefore, efforts are being made to increase crop production by using beneficial microorganisms so that they do not have a negative effect on the environment. One of the efforts made in increasing the growth and yield of soybeans is to utilize Plant Growth Promoting Rhizobacteria (PGPR) which is beneficial for plant growth and increase production. This study aims to see the effect of PGPR on soybean crop productivity. The types of PGPR used were P. agglomerans and E. cloacae which were applied to soaking soybean seeds before planting and applying liquid formula fertilizer at the beginning of growth. From the observed variables, number of pods per plant, number of pods filled per plant, number of seeds per pod, weight of 1000 grains of oven-dried soybeans, oven-dried seed weight per plant, yield of oven-dried seeds per hectare, weight of oven-dried plant canopy dan harvest index. Application P. agglomerans and E. cloacae increase yields of soybeans. Treatment of P. agglomerans and E. cloacae had a very significant effect on most of the observed growth parameters, except for the variable oven-dried weight of plant canopy